On the method demonstrating existence of eigenvalues for a differential operator with boundary conditions dependent on parameter - Strelicas, Š.; Degutis, J. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ш. И. Стрелиц, Ю. Э. Дегутис. Об одном методе доказательства существования собственных значений для одного дифференциального оператора с краевыми условиями, зависящими от параметраŠ. Strelicas, J. Degutis. Apie vieną diferencialinio operatoriaus su kraštinėmis sąlygomis, priklausančiomis nuo parametro, nuosavų reikšmių egzistavimo įrodymo metodą